MAQĀṢID AL-SHARĪʽAH: MEANING, SCOPE AND RAMIFICATIONS - Mohamed El-Tahir El-Mesawi (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2020)
This paper presents a prelude, an overview that sheds light on the theoretical underpinnings and historical development of the concept of maqāṣid al-Sharīʽah in the context of Islamic legal theory (ʽilm uṣūl al-fiqh) which touches on methodological and epistemological issues. The bulk of this essay then undertakes a relatively detailed analysis and explication of the substance, content and dimensions of maqāṣid al-Sharīʽah with the clear intention to highlight the relationship of the idea of maqāṣid to the issue of human nature and its bearing on the question of values. It reflects on the general import and ramifications of maqāṣid al-Sharīʽah with regard human life and development in their complex and multifaceted nature.